The only guide to alternative investments you'll ever need the good, the flawed, the bad, and the ugly - Swedroe, Larry E. (Bloomberg Press, 2008)
"Investors are actively seeking investment options other than equities, bonds, and cash that will provide diversification and improved returns. The book offers an overview of a wide range of alternative investments, explaining what each is and how it works. The author shares his opinions on which to seriously consider and which to avoid at all costs"--Provided by publisher.